ETHNOLINGUISTIC STUDY OF MALAY KITCHEN UTENSILS LEXICON IN BELARAS BARAT MANDAH INDRAGIRI HILIR: KAJIAN ETNOLINGUISTIK LEKSIKON PERALATAN DAPUR MASYARAKAT MELAYU BELARAS BARAT MANDAH INDRAGIRI HILIR - Firma Elena Hidayanti; Yulia Sri hartati; Wahyudi Rahmat (LLDIKTI Wilayah X, 2025)
This study is initiated by the use of lexicons that are closely associated with the cultural development of a community. Employing an ethnolinguistic perspective, this research aims to describe the lexicon of kitchen utensils used by the Malay community in Belaras Barat Village, Mandah District, Indragiri Hilir Regency. The data were analyzed using distributional and referential methods. The results indicate that the lexicon of kitchen utensils is realized in the form of both single words and phrases. From a semantic perspective, the lexicon encompasses utensils for processing and storing food. These lexical items convey not only literal meanings but also reflect local cultural values and traditional knowledge deeply rooted in the daily life of the community. Therefore, the lexicon of kitchen utensils functions as both a linguistic resource and a cultural representation of the Malay society in the research setting.